The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1163/156854003322381531
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cooking and freezing on the carapace length of the American lobster, Homarus americanus H. Milne Edwards, 1837

Abstract: In the southern Gulf of St. Lawrence, there were concerns that freezing seized American lobster (Homarus americanus) to preserve evidence for the court could potentially reduce the carapace length, and compromise the enforcement of a fishery regulation limiting minimal legal size. Tests were performed on 30 soft-and 30 hardshell American lobsters to study the potential for shrinkage when lobsters were cooked and/or frozen. It was found that carapace length reduction was related to the carapace condition. Excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Ibbott et al (2001) found that cooking had no statistically detectable effect on the carapace length of the rock lobster, Jasus edwardsii (Hutton, 1875) noting that discrepancies between repeated measurements were due to measurement error and the difficulty in measuring live animals. More recently, Mallet (2003) andMelville Smith &Thomson (2003) studied shrinkage in the lobsters, Homarus americanus H. Milne Edwards, 1837 and Panulirus cygnus George, 1962, respectively, and found that these species decreased in size marginally as a result of cooking and freezing. In the case of crabs, Williams & Lee (1980) have reported the effects of cooking and freezing on the size of the mud crab, Scylla serrata (Forskål, 1775), and found that neither process affected the size of the rigid exoskeleton.…”
mentioning
confidence: 99%
“…Ibbott et al (2001) found that cooking had no statistically detectable effect on the carapace length of the rock lobster, Jasus edwardsii (Hutton, 1875) noting that discrepancies between repeated measurements were due to measurement error and the difficulty in measuring live animals. More recently, Mallet (2003) andMelville Smith &Thomson (2003) studied shrinkage in the lobsters, Homarus americanus H. Milne Edwards, 1837 and Panulirus cygnus George, 1962, respectively, and found that these species decreased in size marginally as a result of cooking and freezing. In the case of crabs, Williams & Lee (1980) have reported the effects of cooking and freezing on the size of the mud crab, Scylla serrata (Forskål, 1775), and found that neither process affected the size of the rigid exoskeleton.…”
mentioning
confidence: 99%